Competitive interactions between ectomycorrhizal and saprotrophic fungi on chestnut tree - Pereira, Eric (2011)
In Northeast of Portugal the macrofungal community associated to chestnut tree (Castanea sativa is rich and diversified. Among fungal species, the ectomycorrhizal Pisolithus tínctorius and the saprotroph Hypholoma fasciculare are common in this habitat. The aim of the present work was to assess the effect of the interaction between both fungi on growth, nutritional status and physiology of C. satíva seedlings. In pot experiments, C. satíva seedlings were inoculated with P. tínctorius and H. fasciculare individually or in combination. Inoculation with P. tinctorius stimulated the plant growth and resulted in increased foliar-N, -P, and photosynthetic pigment contents. These effects were suppressed when H. fasciculare was simultaneously applied with P. tínctorius. This result could be related to the inhibition of ectomycorrhizal fungus root colonization as a result of antagonism or to the competition for nutrient sources. If chestnut seedlings have been previously inoculated with P. tinctorius, the subsequent inoculation of H. fasciculare 30 days later did not affect root colonization and mycorrhization benefits were observed. This work confirms an antagonistic interaction between ectomycorrhizal and saprotrophic fungi with consequences on the ectomycorrhizal host physiology. Although P. tinctorius is effective in promoting growth of host trees by establishing mycorrhizae, in the presence of other fungi it may not always be able to interact with host roots due to an inability to compete with certain fungi.